ANALISIS YURIDIS TERHADAP PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA KORUPSI YANG DILAKUKAN SECARA BERSAMA-SAMA: ANALISIS YURIDIS TERHADAP PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA KORUPSI YANG DILAKUKAN SECARA BERSAMA-SAMA - Ricky Endy Khe; Theo Ariel Simatupang; Immanuel Saragi; Rahma yanti (Jurnal Cahaya Keadilan, 2020)
Responsibility by corruptors who carried corruption even individually or together is very important thing if we want to against corruption and give them a deterrent effect on corruptors. In Indonesia, corruption is an extraordinary crime, so it requires extraordinary punishment. This can be seen in the legislation that provides space in punishing and eradicating state losses, namely in Regulation Number 31 of 1999 Jo. Regulation Number 20 of 2001 about Eradication of Corruption. The method used in this study is a normative juridical research method, by collecting data in a literature review by research about legal norms in regulation about corruption. This study is works to searching and looking more for regulation in the context of the Responsibility of Corruption Criminals Conducted Together. The results of the research are that corruption is carried out by a person or group of people influenced by some factors, and as a result of corrupt actions, then responsibility can be imposed on the